The study of consistent properties of gelatinous shampoo with minoxidil - I. V. Gnitko; V. V. Gladishev; A. P. Lisyanskaya; I. A. Biriuk (Aktualʹnì Pitannâ Farmacevtičnoï ì Medičnoï Nauki ta Praktiki)
The aim of the work is the study of consistent properties of gelatinous shampoo with minoxidil 1% for the complex therapy and prevention of alopecia. This shampoo with minoxidil was selected according to the complex physical-chemical, biopharmaceutical and microbiological investigations.